1990
DOI: 10.1016/0741-5214(90)90278-i
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of a gram-negative and a gram-positive infection on autogenous and prosthetic grafts

Abstract: A canine model was developed to study the differential response of a gram-negative and a gram-positive bacterial infection on autogenous and prosthetic grafts. After replacing segments of the femoral arteries of 15 dogs with autogenous vein in one groin and polytetrafluoroethylene in the contralateral groin, 108 colony-forming units ofnonmncinproducing Staphylococcus epidermidis (five dogs), Pseudomonas aeruginosa (five dogs), or sterile saline solution (five dogs) were directly inoculated onto the grafts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 26 publications
(5 reference statements)
0
29
0
Order By: Relevance
“…Although some authors did not observe worse outcomes with Pseudomonas infection, 5,10 others have reported increased amputation rates or poorer graft salvage. 7,8,31 Calligaro et al 7 reported only 40% graft salvage when the offending organism was Pseudomonas. Pseudomonas infection was associated with 60% limb loss in a series reported by Seify et al 8 Since both our patients with Szilagyi III infections with Pseudomonas infections eventually needed graft removal, we now recommend graft removal in early Pseudomonas groin infections with exposed grafts.…”
Section: Discussionmentioning
confidence: 98%
“…Although some authors did not observe worse outcomes with Pseudomonas infection, 5,10 others have reported increased amputation rates or poorer graft salvage. 7,8,31 Calligaro et al 7 reported only 40% graft salvage when the offending organism was Pseudomonas. Pseudomonas infection was associated with 60% limb loss in a series reported by Seify et al 8 Since both our patients with Szilagyi III infections with Pseudomonas infections eventually needed graft removal, we now recommend graft removal in early Pseudomonas groin infections with exposed grafts.…”
Section: Discussionmentioning
confidence: 98%
“…30,37,39 Arterial dissolution with aneurysm formation is more frequently encountered in infections with virulent organisms such as Pseudomonas or S aureus. [49][50][51] Grafts with convincing clinical findings of infection that produce no growth with standard culture techniques may occur as frequently as 25%. 47,48 This inconsistency is often attributed to preoperative antibiotic administration.…”
Section: Pathophysiology and Diagnostic Evaluationmentioning
confidence: 98%
“…[12][13][14] The reason for its pathogenicity probably lies with its capacity to adhere to the endothelium (via pili), resist phagocytosis (via mucoid exopolysaccharide capsule), and generate vascular disruption (via elastase and alkaline protease). 12,13,15 Moreover, Pseudomonas is very difficult to clear, possibly because of the organism's adaptability, minimal nutritional requirements, and relative antibiotic resistance. 12,13,15 The clinical presentation of infected aneurysm can be varied and subtle.…”
Section: Discussionmentioning
confidence: 99%